Effect of Different Parameters on Gelatin Adsorption and Stability of the Colloidal Dispersion of Gelatin-Coated Magnetic Iron Oxide Nano-Particles - Babita Gaihre; Daman C. Parajuli; Hae C. Seo; Myung S. Khil; Hak Y. Kim (Adsorption Science & Technology)
In this study, magnetic iron oxide nano-particles (IOPs) of ca. 8 nm in size were coated with gelatin A or B. The effect of temperature, pH, incubation time and salinity on the adsorption of the polymer coating was studied. The effect of pH and salinity on the stability of the colloidal dispersion was also studied using the inductive plasma coupling technique by measuring the concentration of IOPs present in the dispersion after 24 h incubation under specified conditions. The results showed that the adsorption of gelatin B was greater relative to that of gelatin A, probably as a result of the presence of a comparatively large number of free carboxylic groups. The adsorption phenomenon was affected by temperature, pH, incubation time and the salinity of the medium. However, it was observed that the concentration of IOPs in the dispersion was not drastically affected after incubation under given conditions of pH and salinity, thereby demonstrating the stability of the colloidal dispersion as a result of steric stabilization by gelatin. The dispersions were stable for a minimum of 24 h without any visual precipitation.